Las TIC’s en la formación de los docentes - Pastuña Iza, Nancy Mélida (2016)
The Society is in a time of hasty changes in science and technology, thus evolving knowledge, technological tools and how to fill in different teaching activities that is done every day the teacher, for this reason the teacher should emphasize the use of technological tools in vocational training. Thus the use of technological tools was diagnosed by teachers through research to facilitate the work of teachers in the education system, where it is essential to apply the deductive method to obtain the expected results in teachers, so both the current education is needed that this teacher constantly updated in different areas of study to use various teaching strategies. In this research was used as a technique and as an instrument survey questionnaire where possible to detect the main aspects in which teachers have higher strengths and where they need to improve. As a result of this, you can outline some strategies or specific actions for treatment in the institution. Therefore the information technology and communication are essential in the teaching-learning process, because through these tools the teacher has the opportunity to create an enabling environment and enrich the knowledge of students in the educational context. It is noteworthy that the teacher's role is not only to teach the class traditionally, but must perform various activities using different technologies in the classroom. Consequently it provided different alternatives of the traditional model, with the use of technological tools that is responsible for teacher training and student, while the teacher justify to follow an updated class to provide training properly.